PENGAMBILAN KEPUTUSAN KOMPONEN DARAH DALAM PENGENDALIAN PERSEDIAAN DENGAN MENGGUNAKAN METODE AHP DI PMI KOTA BANDUNG - Muchammad Fauzi; Senator Nur Bahagia (Universitas Widyatama, 2019)
PMI of Bandung City experienced overstock. Overstock and expired blood supplies must be destroyed. In the overstock phase every month, PMI of Bandung City experiences waste and needs to be controlled inventory. In the blood have six components that need to be controlled, but it takes a long time to analyze each component of the bloood. It is necessary to determine the priority blood components that must bee controlled immediately so that they are expected to influence the reduction in the destroyed cost. The purpose of this study is find out what blood component are prioritized to control their supply. Determination of blood component priority using the AHP (Analitycal Hierarchy Process) approach. The AHP method is decision making model that breaks down complex multi-criteria problems into a hierarchy. The priority blood component to be controlled is Packed Red Cell (PRC) component of 0.338. This value is obtained because it is influenced by the weight of the supply criteria of 0.709, demand of 0.113; and lifetime of 0.179.